Psychological approach to choosing a spouse for young people who are about to start a family - Tulkinboeva is Makhliyo (Periodica Journal, 2023)
In this article, the results of the research are explained in order to provide psychological services to young people who are about to start a family. In the current period, in order to strengthen family relations and further develop interpersonal relations, psychological services are the need of the hour to guide young people in the right way in choosing a spouse. The main goal is to find out to what extent they are ready for a family, and to provide practical help in choosing the right spouse
Keywords: Family; young families; psychological service; present time